Odpowiedzi

2010-04-09T09:36:31+02:00
1/2*(0,1+0,1)+1/3*(0,1+0,2)+1/4*(0,2+0,2)=
1/2*(0,2)+1/3*(0,3)+1/4*(0,4)=
0,1+0,1+0,1=0,3
2010-04-09T09:37:11+02:00
1/2*(0,1+0,1)+1/3*(0,1+0,2)+1/4*(0,2+0,2)=

= (1/2) * (2/10) + (1/3) * (3/10) + (1/4)*(4/10)=

=1/10 + 1/10 + 1/10 = 3/10 = 0,3
2010-04-09T09:38:25+02:00
1/2*(0,1+0,1)+1/3*(0,1+0,2)+1/4*(0,2+0,2)=
1/2 x 0,2 + 1/3 x 0,3 + 1/4 x 0,4 =
1/2 x 2/10 + 1/3 x 3/10 + 1/4 x 4/10 =
2/20 + 3/30 + 4/40 =
12/120 + 12/120 + 12/120 =
1/10 + 1/10 + 1/10 =
0,1 + 0,1 + 0,1 =
0,3 = 3/10